Feasibility and safety of dilatational tracheotomy using the rigid endoscope: a multicenter study. Issue 1 (December 2017) - Nowak, Andreas; Kern, Peter; Koscielny, Sven; Usichenko, Taras; Hahnenkamp, Klaus; Jungehülsing, Markus; Tittel, Matthias; Oeken, Jens; Klemm, Eckart
Abstract Background Fiberoptic tracheo-bronchoscopy is the most commonly used procedure for percutaneous dilational tracheotomy (PDT). However, PDT can be associated with major complications, including death. Furthermore it is unclear, whether the tracheal ring fractures may contribute to the development of tracheal stenosis after PDT nor whether tracheal ring fractures can be prevented by using a rigid endoscope for this procedure. The purpose of this study was to evaluate the feasibility of and the incidence of complications for PDT using the rigid tracheotomy endoscope (TED). Methods In a prospective multicenter observational study from 2006 to 2010, 180 adult patients in intensive care and those scheduled for ear, nose and throat surgery underwent PDT using TED. Data collection was performed using a structured protocol. The patients were observed according to PDT phase (phase 1: puncture, phase 2: dilatation and phase 3: cannula insertion). The descriptive data are given as the number (percent) of cases and the mean ± standard deviation (SD) where appropriate. The relationships between dichotomous and categorical parameters were analyzed using the chi-square test.P values ≤ 0.05 were considered significant. Results PDT was performed in 179 patients. The procedure time was 14.8 ± 6.2 (mean ± SD) minutes. Pneumothorax or procedure-related lethal complications did not occur. Other adverse events included tracheal ring fractures (17.1%), desaturations (6.8%), special incidents (6.2%), bleeding (5.5%), anesthesia complications (4.5%) and posterior tracheal wall injuries (1.1%). Conclusion The use of TED in PDT is feasible, and the incidence of complications and adverse events was comparable with that of PDT using the flexible endoscope. Tracheal ring fractures in PDT cannot be avoided by the use of a rigid endoscope. With TED, the airway always remains open thus the use of jet ventilation via the TED during PDT is possible.